2021
DOI: 10.1155/2021/4156904
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Intelligent Rural Tourism Service by Neural Network Algorithm Models

Abstract: With the continuous development of social economy, tourism has become one of the many choices and is becoming more and more popular. However, it should be noted that how to provide high-quality and efficient tourism services is extremely important. This paper introduces the neural network algorithm and the optimal classification decision function, through unified combing, classification, and coding of scenic spots, to achieve the subclass classification of scenic spots, based on the optimal distribution functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The GIS system allows users to create maps and other visual representations of data, which can be used to identify patterns and relationships. The system also allows users to create simulations, which can be used to test scenarios and evaluate the impact of different decisions [14].…”
Section: Geographic Informationmentioning
confidence: 99%
“…The GIS system allows users to create maps and other visual representations of data, which can be used to identify patterns and relationships. The system also allows users to create simulations, which can be used to test scenarios and evaluate the impact of different decisions [14].…”
Section: Geographic Informationmentioning
confidence: 99%
“…The proposed model is put into practice and evaluated in Shanghai, and the results show that compared with the traditional model, the proposed model has better performance and can generate three-dimensional trajectories of tourists. Literature [20] introduces a neural network algorithm and optimal classification decision function to realize the classification of subclasses of attractions and then combines it with the optimal distribution function of random intelligent selection to generate clear attraction travel routes. Simulation experiments have demonstrated the feasibility of the proposed scheme, which can aid in decisionmaking regarding rural tourism services.…”
Section: Introductionmentioning
confidence: 99%
“…Chen, J. et al, based on the optimal classification decision function and neural network algorithm to encode and classify scenic area information, to achieve intelligent random selection within the database and to form intelligent optimization of clear scenic area travel routes, the study show that this intelligent decision-making system helps to optimize the rural tourism services [11]. Sports activities have a certain impact on economic benefits; Li, G. et al studied the relevant impact of sports tourism on the economy in terms of revenue and economic value added, selected two regions of Castile and Leon region to analyze the sports tourism economy, and concluded that the sports tourism industry has a greater impact on the regional economy [12].…”
Section: Introductionmentioning
confidence: 99%